Exploring high school teachers’ experiences of problem-based learning implementation on buffer solution - F N Azizah; M Rosbiono; W Sopandi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Problem Based Learning (PBL) as one of the innovative learning models designed to enable students to be actively involved in the process of obtaining information, knowledge and problem solving. This descriptive study aims to collect information of methods often used by teachers, and the implementation of PBL on buffer solution concept. The data source comes from 20 high school chemistry teachers of class XI. Data were collected using interview guidance instruments and then processed in accordance with research questions. The results showed that teachers often use lecturer method, and most teachers have not yet used the PBL model on buffer solution and do not know the proper syntax. These findings indicate how we need application of PBL on buffer solution concept.